Cybersecurity and Sovereignty in Cyberspace: Challenges and Prospects of International Law - С. С. Lazari (Московский журнал международного права)
INTRODUCTION. This article explores the concept of “cyber sovereignty”, understood as the set of legal claims and mechanisms through which states seek to control and protect their interests in the digital domain. Amid the rapid development of information and communication technologies, the transnational nature of cyberspace, and the lack of unified international norms, debates on the applicability of classical state sovereignty to the digital realm are intensifying. The paper examines various approaches taken by different countries (Russia, China, the United States, EU member states, etc.) in regulating cyberspace, highlighting the growing importance of cybersecurity in international law, and analyzing the role of international organizations (including the UN) and key documents such as the Tallinn Manual 2.0.MATERIALS AND METHODS. The study is based on a qualitative analysis of academic literature, international legal instruments (UN Charter, International Court of Justice rulings, doctrinal documents), national cybersecurity strategies (Russia, the USA, China, among others), and a comparative examination of state practices and positions regarding cyber sovereignty. General and specific scientific methods – analysis and synthesis, systematic and comparative-legal approaches – were employed to identify legal gaps and contradictions in the regulation of the digital environment.RESULTS. The analysis shows that states increasingly aim to extend the concept of classical sovereignty to cyberspace by developing national legislation and creating independent cyber jurisdictions. This trend is reflected in the strategies and doctrines of several countries (China, Russia), which seek to control their segment of the internet. At the same time, a rift remains between states that advocate for an open and free internet (the USA, EU states) and those that prioritize strengthening national control over the digital sphere. In practice, it is difficult for states to reach consensus on the permissible scope of intervention and the application of the principles of non-intervention and sovereignty in cyber operations.DISCUSSION AND CONCLUSIONS. The analysis reveals legal uncertainty in defining what kinds of cyber operations violate sovereignty, as well as in the categorization of cyber espionage and low intensity cyberattacks. The UN and its specialized expert groups (GGE, OEWG) are working on harmonizing approaches; however, no single universal mechanism has yet been established. The most acute controversies concern recognizing sovereignty in the digital sphere as a distinct norm of international law and establishing clear criteria for legitimate cyber operations. Overcoming legal gaps and reducing the risk of conflict require the development of universal principles that account for the unique characteristics of cyberspace, as well as the deepening of international cooperation, including the exchange of information and the creation of rapid response mechanisms to cyber threats.